System religijny w dobie globalizacji. Inkluzja i fundamentalizm z perspektywy teorii systemowej Niklasa Luhmanna - Dziuban, Agata (Poznańskie Studia Teologiczne, 2008)
The aim of this article is to examine the phenomena of inclusion and fundamentalism within Niklas Luhmann’s system theory of religion in a globalized society. According to system theory, functional differentiation, rising contingency, and progressing specialization of decision-making centers within western society have all lead to the emergence of a modem and, subsequently, globalized society. Due to changes in the social system, followed by the process of secularization, religion has differentiated itself into an autonomous social subsystem. In effect, it has lost its central position as a value provider and encompassing normative system. Rising religious inclusion and privatization, as well as the emergence of religious fundamentalism, are seen as two opposing, yet complimentary, processes, each emerging as a consequence of modernization and globalization. Inclusion is understood as an individual’s ability to chose between a variety of possible religious options, without the threat of facing any religious or social sanctions. Conversely, fundamentalism is seen as a radical reaction to the process of modernization and progressing differentiation of the social and religious system. From Luhmann’s perspective, both of these processes can lead to the disintegration of religious and, as a consequence, the social system as a whole.